Audit Findings as a Moderator in Financial Disclosure Determinants in the Public Sector - Sujatmiko, Fajar; Bawono, Andy Dwi Bayu; Witono, Banu (LPPM Universitas PGRI Sumatera Barat, 2024)
Despite the establishment of national regulations to guide financial disclosure, there are still gaps in how local governments report financial information. This study aims to determine the contribution of capital expenditure, fiscal independence ratio, local government size, and legislative size to the disclosure of Local Government Financial Reports (LKPD) in Indonesia. With a positivist epistemology perspective, this analysis applies a quantitative approach with secondary data from 113 district and city governments in Java Island, resulting in 226 observations. Eight hypotheses are tested using multiple linear regression and moderation analysis. Classical assumption tests (e.g., normality, multicollinearity, and heteroscedasticity) are run on the data. The results show that fiscal autonomy and board size are significantly related to LKPD disclosure. However, investment and local government scale are not significant as the main predictors. Furthermore, the effect of audit reports in moderating the relationship between financial indicators and the level of information disclosed is not significant. This finding reflects the dominance of governance-related aspects over structural dimensions (e.g., organizational size) in predicting transparency. This study is repeated because it identifies audit findings as a moderating variable on the relationship between financial governance and public disclosure, a stance that is rarely studied in the Indonesian public finance literature. These findings suggest that improving governance quality and audit performance is more effective in encouraging financial disclosure than structural expansion. The novelty of this study offers suggestions to public administrators and audit institutions seeking to improve financial accountability.